The Acceptance Analysis of Financial Accounting Standards for Entities Without Public Accountability (Fas-Ewpa) in Cirebon Regency Cooperatives Using Technology Acceptance Model (Tam) - Permana, Intan; Thomas, Partono; Kardoyo, Kardoyo (Journal of Economic Education, 2019)
The Indonesian Government has ratified Financial Accounting Standards for Entities without Public Accountability (FAS-EWPA, in bahasa Indonesia known as SAK-ETAP) in 2009 as guidelines for financial reporting for entities without public accountability, one of which is cooperative (koperasi).The large number of cooperatives in Cirebon Regency that have carried out annual member meeting but lacking implementation of FAS-EWPA is still considered as a constraint. The purpose of this study is to analyze the acceptance of cooperative administrators towards FAS-EWPA using Technology Acceptance Model (TAM). This research uses a quantitative method with path analysis using SPSS 20.0 for windows and Sobel Test Calculator to determine the significance of intervening variables. The number of population in this study is 193 cooperatives in Cirebon Regency with a total sample of 65 cooperatives. The results of this study indicates positive correlations on : education towards perceived usefulness, perceived ease, and intention to use; subjective norms toward perceived usefulness and perceived ease; organizational factors toward perceived usefulness, perceived ease, and intention to use; perceived usefulness towards intention to use; and perceived ease towards intention to use.There is no correlation between subjective norms and intention to use. The difference between this research and several previous studies is that the use of external variables such as education and organizational factors influencing TAM is rarely used in previous studies.